Development of H2O2 Based Mixed Hybrid Rocket. Issue 11 (4th August 2021) - Marothiya, Gaurav; Ramakrishna, P. A.; Saravanan, N.; Kumar Solasa, Praveen
Abstract: As a green oxidizer, hydrogen peroxide is an earth‐storable, non‐toxic liquid oxidizer. This study shows a possible combination of wax‐based aluminized fuel with hydrogen peroxide as an oxidizer, which can be used to improve the specific impulse and density specific impulse of the hybrid rockets. In this study, various methods have been tried to ignite the hybrid rocket and measure the regression rates and ballistic performance. This research presents sustainable combustion of hydrogen peroxide with aluminized wax‐based fuel without the need for any catalyst bed. This combination of hybrid propellant demonstrates superiority over other fuels with hydrogen peroxide and shows promises in terms of an option as the future green propellant. The theoretical specific impulse of about 315  s at 100 bar with a nozzle exit area ratio of 50 is shown by this fuel and oxidizer combination. Another benefit of this combination of hybrid propellant is that the peak specific impulse is obtained at an O/F ratio of almost unity which makes the system more compact. Abstract :